Tari Tanggai dan Habitus Masyarakat Palembang - Muhammad Juniussava Saputra; Ridhah Taqwa Ridhah; Faisal Nomaini Faisal (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
Culture is a phenomenon that will always exist in every layer of society . people tend conceptualization of values and norms that exist in society into cultural forms that exist . One element of culture that always exist in society , namely art . Every region in Indonesia there are a variety - variety type of art ranging from being blown up the limb as demonstrated . one culture there is the art of dance . In Indonesia , there are various protean dance that spread from Sabang to marauke , one of which is tanggai dance contained in Palembang of South Sumatra Province . Tanggai dance hidden inside habitus that exist in society Palembang . Habitus is used as the basis for Palembang people to act and interpret the world in their daily reality . The habitus is in tanggai dance : first , the dance represents the orientation of life and values of the people of Palembang . Secondly , dance as a picture kinship systems Palembang society .